Expanding flavone and flavonol production capabilities in Escherichia coli - Yiakoumetti, Andrew; Hanko, Erik K. R.; Zou, Yutong; Chua, Jeremy; Chromy, Jakub; Stoney, Ruth A.; Valdehuesa, Kris Niño G.; Connolly, Jack A.; Yan, Cunyu; Hollywood, Katherine A.; Takano, Eriko; Breitling, Rainer (Frontiers in Bioengineering and Biotechnology, 2023)
Flavones and flavonols are important classes of flavonoids with nutraceutical and pharmacological value, and their production by fermentation with recombinant microorganisms promises to be a scalable and economically favorable alternative to extraction from plant sources. Flavones and flavonols have been produced recombinantly in a number of microorganisms, with Saccharomyces cerevisiae typically being a preferred production host for these compounds due to higher yields and titers of precursor compounds, as well as generally improved ability to functionally express cytochrome P450 enzymes without requiring modification to improve their solubility. Recently, a rapid prototyping platform has been developed for high-value compounds in Escherichia coli, and a number of gatekeeper (2S)-flavanones, from which flavones and flavonols can be derived, have been produced to high titers in E. coli using this platform. In this study, we extended these metabolic pathways using the previously reported platform to produce apigenin, chrysin, luteolin and kaempferol from the gatekeeper flavonoids naringenin, pinocembrin and eriodictyol by the expression of either type-I flavone synthases (FNS-I) or type-II flavone synthases (FNS-II) for flavone biosynthesis, and by the expression of flavanone 3-dioxygenases (F3H) and flavonol synthases (FLS) for the production of the flavonol kaempferol. In our best-performing strains, titers of apigenin and kaempferol reached 128 mg L −1 and 151 mg L −1 in 96-DeepWell plates in cultures supplemented with an additional 3 mM tyrosine, though titers for chrysin (6.8 mg L −1 ) from phenylalanine, and luteolin (5.0 mg L −1 ) from caffeic acid were This is a provisional file, not the final typeset article considerably lower. In strains with upregulated tyrosine production, apigenin and kaempferol titers reached 80.2 mg L −1 and 42.4 mg L −1 respectively, without the further supplementation of tyrosine beyond the amount present in the rich medium. Notably, the highest apigenin, chrysin and luteolin titers were achieved with FNS-II enzymes, suggesting that cytochrome P450s can show competitive performance compared with non-cytochrome P450 enzymes in prokaryotes for the production of flavones.